Hand hygiene practices in the context of Ebola virus disease: A cross-sectional survey of Lagos residents. Issue 4 (July 2019) - Akinyinka, Modupe R; Bakare, Omowunmi Q; Oluwole, Esther O; Odugbemi, Babatunde A
Background: The Ebola virus disease outbreak that ravaged parts of West Africa has been described as the most severe acute public health emergency seen in modern times. Hand washing was promoted among other measures for infection prevention. Objective: This study assessed the awareness of Ebola virus disease and hand-washing practices among Lagos residents, southwest Nigeria. Methods: A descriptive cross-sectional study was used. A total of 1982 respondents aged 18 ⩾ years were selected using a multi stage sampling technique. An interviewer-administered, pre-tested questionnaire was used for data collection between August and November 2015. Data were analysed using the Statistical Package for Social Sciences (SPSS) version 22, with level of significance set at 0.05. Results: Almost all (97.3%) respondents were aware of Ebola virus disease, with over half of respondents having heard about it from television. A majority of 1890 (95.4%) respondents were aware of the importance of hand washing in disease prevention. Similarly, high proportions of respondents were aware they should wash their hands after an outing, toilet use, touching pets, before and after meals, while 1628 (82.1%) of respondents knew to wash their hands after a hand shake. However, less than half of respondents (38.8%) always washed their hands after handshakes. Discussion: A majority of respondents surveyed were aware of Ebola virus disease and hand washing, but the practice of hand washing, which is key in prevention of infection, lagged behind the knowledge of the respondents.